Analysis of Determining the Leading Sectors of the Regional Economy of Labuhan Batu Regency: LQ and Shift Share Approach - Penus Leonard Roningsih Sinurat; Vivi Safira; Melvany Agustini Sinurat (Outline Publisher, 2025)
This study aims to analyze economic growth in Labuhan Batu Regency using the Gross Regional Domestic Product (GDP) as the main indicator. The methods used include Location Quotient (LQ) analysis to identify base and non-base sectors, as well as Shift Share analysis to evaluate the economic growth components of each sector between 2019 and 2023. The results of the analysis show that the Processing and Construction Industry sector is a base sector with an LQ value above one, while other sectors are classified as non-base, which shows the potential for competitiveness that has not been utilized. The secondary data used shows that the GDP of Labuhan Batu Regency is still small compared to the total GDP of North Sumatra Province, indicating the need for a more effective development strategy to increase regional economic growth.